Germinação de sementes e mobilização de reservas em plantas de copaíba sob estresses hídrico e salino. - Amaro, Manoel Silva (2012)
The objective of this research was to evaluate different techniques for breaking dormancy, the germination under saline conditions and drought, the development of seedlings subjected to different potentials of solutes and NaCl stress conditions relate to the cotyledonary reserve mobilization in seedlings Copaifera langsdorffii. The treatments of over come consisted of immersion in water/24, 48 and 72 h, hot water, 50, 75 C and boiling water/10’, 15’ and 20’ and H2SO4 (98,08%)/15, 30’ and 60’ min and control. For stress conditions, the seeds were immersed in 100 ml of NaCl or PEG 6000 with a potential of the solute, [0,0 (control), -0,2, -0,4, -0,6, -0,8 and -1,0 MPa]. The water absorption, was evaluated (168 h) germination percentage (G%), germination speed index (GSI) and mean germination time (MGT). For the mobilization of the reserves were used as the same solute potential with NaCl above. Sowing was on paper germitest and germination in a germination chamber of the BOD at 25 ºC and photoperiod of 12 h, consisting of five replicates of 25 seeds per treatment. Studies of the effects of NaCl was done in three stages of developing an ED (radicle with 5 ± 2 cm) ED 2 (issuing protophilus) and ED 3 (protophilus expanded), taking as reference quiescent seeds (DE 0). 15 seedlings per replicate were separated into cotyledons and axis. Quantified the dry mass of cotyledons and axis, the levels of lipids, proteins, starch, soluble sugars, amino acids and Na+, K+ and Cl-. We evaluated the activities of enzymes: lipase, the isocitrate lyase, malate synthase, α and β-amylases and starch phosphorylase in the cotyledons of seedlings grown in distilled water and in NaCl solutions with solute potential of -0,4 and -0,8 MPa. The water absorption by seeds copaiba was higher and faster in the treatments with boiling water and sulfuric acid. The PEG 6000 and NaCl delayed the time of soaking, Overall, the immersion in H2SO4 performed best in breaking dormancy. In stressful conditions, NaCl had no influence on %G, however, reduced the (IVG) and increased the TMG, the solute potential of -0,6, -0,8 and -1,0 MPa. PEG reduced the %G in solute potential of -0,8 and -1,0 MPa and had a greater effect on IVG and TMG, compared with NaCl. The seeds were quiescent lipids as the main reserve. The increase in salinity inhibited the mobilization of reserves in the cotyledons of the seeds, especially in the solute potential of -0,8 and -1,0 MPa and increasing the concentrations of Na+ and Cl- in the embryonic axis and cotyledons. Inhibition of the mobilization of reserves caused by salt provided an increase in soluble sugars in the cotyledons, this effect inhibited the growth and seedling development. The activities of enzymes in the metabolism of lipids and of starch phosphorylase were significantly inhibited with increasing salinity, with more effectively inhibited the enzymes of lipid metabolism. The seeds have a strong resist entry of water, the immersion of the seed in concentrated sulfuric acid for 60’ is effective to remove the barrier. For %G, the copaiba seeds under conditions that were tested are NaCl-tolerant and intolerant to PEG. The germination is less sensitive than the NaCl seedling stage. The NaCl in solute potential below -0,4 MPa negatively affects the growth and early development of seedlings of copaiba.